Effectiveness of central bank intervention on the foreign exchange market - Karl Finger; Stefan Reitz (Kiel Institute for the World Economy (IfW), 2012)
In contrast to academic recommendations monetary authorities all over the world intervene on the foreign exchange market to actively manage the exchange rate. Particularly in the aftermath of the global financial crisis the exchange rate is abused by some countries in a currency war to artificially improve the own competitiveness and thereby harming trading partners. Aside from these heavily debated activities a number of open economies try to shield their currency from irrational exuberance of international investors and use interventions to maintain exchange rates around their fundamental levels. This study shows theoretically and empirically how intervention operations can be effective in the latter sense. – – Entgegen akademischer Empfehlungen intervenieren Währungsbehörden auf der ganzen Welt jeden Tag auf den Devisenmärkten um den Wert ihrer Währung zu beeinflussen. Besonders nach der globalen Finanzkrise wird der Wechselkurs von einigen Ländern dazu missbraucht, um die eigene Wettbewerbsfähigkeit in einem Währungskrieg zu steigern und damit Handelspartnern zu schaden. Neben diesen intensiv diskutierten Maßnahmen versuchen einige Länder ihre Währung vor irrationalen Übertreibungen internationaler Investoren zu schützen und nutzen Interventionen, um Wechselkurse in der Nähe ihrer Fundamentalwerte zu halten. Diese Studie zeigt theoretisch als auch empirisch, wie Interventionen im letzteren Sinn effektiv sein können.
Keywords: 330